Improving the Ability of Listening and Writing in Chinese Using Dictation Methods in Learning - Iden, Sabinus; Surya Wibowo, Albert (KnE Social Sciences, 2023)
The dictation method into learning is one of the ways that Mandarin language educators often use to improve students’ listening and writing skills. This research is a classroom action research which aims to improve the ability to hear and write Mandarin using the dictation method. Collecting data in this study using observation, interview and self assessment methods. The technique used to analyze the data that has been collected is a qualitative descriptive technique. With the dictation method, students’ listening and writing skills increased significantly. Keywords: Dictation method; Chinese; Mandarin language